2013
DOI: 10.1002/pros.22691
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‐related protein 3 promotes pathogenic stromal remodeling in benign prostatic hyperplasia and prostate cancer

Abstract: BACKGROUND Compartment-specific epithelial and stromal expression of the secreted glycoprotein Dickkopf-related protein (Dkk)-3 is altered in age-related proliferative disorders of the human prostate. This study aimed to determine the effect of Dkk-3 on prostate stromal remodeling that is stromal proliferation, fibroblast-to-myofibroblast differentiation and expression of angiogenic factors in vitro.METHODS Lentiviral-delivered overexpression and shRNA-mediated knockdown of DKK3 were applied to primary human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 44 publications
1
38
2
Order By: Relevance
“…The following antibodies were used: β‐catenin, DKK3, cyclin D1, c‐Myc (Santa Cruz Biotech) 18, E‐Cadherin (Epitomics Inc.), vimentin, cleaved caspase‐3, cleaved caspase‐9, cleaved caspase‐7, cleaved PARP, E‐cadherin, vimentin, N‐Cadherin, Histone 1 (Cell Signaling Technology, Danvers, MA, USA) 19, β‐actin (Sigma‐Aldrich) 20, survivin, OCT4 and CD133 (Santa Cruz Biotech) 21, Glyceraldehyde 3‐phosphate dehydrogenase (Abcam) 22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following antibodies were used: β‐catenin, DKK3, cyclin D1, c‐Myc (Santa Cruz Biotech) 18, E‐Cadherin (Epitomics Inc.), vimentin, cleaved caspase‐3, cleaved caspase‐9, cleaved caspase‐7, cleaved PARP, E‐cadherin, vimentin, N‐Cadherin, Histone 1 (Cell Signaling Technology, Danvers, MA, USA) 19, β‐actin (Sigma‐Aldrich) 20, survivin, OCT4 and CD133 (Santa Cruz Biotech) 21, Glyceraldehyde 3‐phosphate dehydrogenase (Abcam) 22.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-cell lysates were prepared using radio immunoprecipitation assay (RIPA) lysis buffer (1% Triton X-100, 1 mmol/l ethylenediaminetetraacetic acid, 100 mmol/l NaF, 1 mmol/l Na 3 VO 4 and protease inhibitor cocktail), and Western blot analyses were performed as described previously [17]. The following antibodies were used: b-catenin, DKK3, cyclin D1, c-Myc (Santa Cruz Biotech) [18], E-Cadherin (Epitomics Inc.), vimentin, cleaved caspase-3, cleaved caspase-9, cleaved caspase-7, cleaved PARP, E-cadherin, vimentin, N-Cadherin, Histone 1 (Cell Signaling Technology, Danvers, MA, USA) [19], b-actin (Sigma-Aldrich) [20], survivin, OCT4 and CD133 (Santa Cruz Biotech) [21], Glyceraldehyde 3phosphate dehydrogenase (Abcam) [22].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…This indicates that Dkk3 acts as a tumor suppressor in kidney cells and that the downregulation of Dkk3 may be involved in RCC progression (16). The expression of Dkk3 has been analyzed in several types of malignancies, and downregulation of Dkk3 has been observed in glioma, breast cancer, melanoma, prostate cancer and gastrointestinal cancer (14,(35)(36)(37)(38). Further studies have revealed that the downregulation of Dkk3 in cancer was a result of epigenetic silencing by DNA methylation (17).…”
Section: A B C Dmentioning
confidence: 99%
“…In malignant cells, DKK3 can function as either a tumor‐suppressor gene or oncogenic factor depending on cell type and context (Zenzmaier et al . ). Moreover, several reports have described increased DKK3 expression in tumor‐associated cells, such as stromal and endothelial cells, where it appears to support differentiation and tissue remodeling and is associated with a favorable prognosis (St Croix et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Zenzmaier et al . ). These data suggest that DKK3 plays a distinct and complex role in cancer cell survival, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 97%